Synthesis of affordable activated carbons from almond shell and almond tree pruning waste for aqueous zinc hybrid supercapacitors - Shaj, Densa Ann; Antorán, Daniel; Alvira, Darío; Manyà, Joan Josep (Jornada de Jóvenes Investigadores del I3A, 2025)
This study focuses on improving biomass-derived carbon materials to be used as cathodes in zinc hybrid supercapacitors. We chemically activated almond shells and almond tree pruning residues through a hydrothermal pretreatment and subsequent carbonisation. We examined the effects of precursor morphology and activating agents on the properties of the resulting carbons. Furthermore, the influence of the type of electrolyte and the use of carbon black as conductive agent on the electrochemical performance was also assessed. The best-performing K2CO3-treated sample achieved 142 mA h g–1 at 0.1 A g–1 with 92 % capacity retention over 2000 cycles at 10 A g–1